Histological and Immunohistochemical Characterization of Vascular Alterations in Meninges of Cats Infected with Gurltia paralysans - Svenja Hartung; Angelika Weyrich; Manuel Moroni; Marcelo Gómez; Christiane Herden (Pathogens, 2022)
Gurltia paralysans, a metastrongyloid nematode, parasitizes in meningeal vessels in the thoracolumbar spinal cord of cats in South America and causes progressive paraparesis. Recently, the first report outside of South America described gurltiosis in a cat in Spain. As this parasitic disease has so far been largely neglected, especially outside of South America, the aim of the present case study was to add knowledge to the histologic and immunohistochemical characterization of central nervous lesions. To this purpose, formalin-fixed and paraffin-embedded (FFPE) tissue samples from the spinal cord and brain of five cats affected by clinical signs caused by Gurltia paralysans and of three control cats without CNS lesions were histopathologically examined using hematoxylin and eosin stain (HE), Elastica van Gieson stain, as well as periodic acid–Schiff (PAS) reaction. Moreover, immuno- histochemistry for alpha smooth muscle actin and Factor VIII-related antigen were performed to characterize vascular lesions. Lesions were consistent with previous descriptions and were mainly located in the spinal cord and consisted of chronic suppurative or lymphoplasmahistiocytic meningi tis as well as suppurative vasculitis, congestion and varicosis of meningeal veins. In view of the recent detection of this parasite in Europe and the increasing inner-European transport of rescued domestic cats, veterinarians in Europe should be aware of the clinical and pathomorphological presentation of this disease.